(untitled) (Revista INTEREDU11, 2021)
The Covid-19 pandemic resumes discussions about exclusionary historical processes produced by racism which has been accelerated, today, by this disease. The purpose of this text is to contextualize the history of education of the Afro-Brazilian people and the role of compensatory actions made possible by national public policies as an attempt to repair centuries of silence for the Afro-descendant population and their contribution to the construction and effectiveness of our culture and society. Here, we highlight the distorted views of this contribution, since we understand that when they are projected on the national scene, they allow the elaboration of significant enquiries, one of them is the importance that Africans and Afro-descendants have had in the construction of our cultural identity. Educational processes must be revised to overcome Eurocentricity and a historical legacy of enslavement and segregation that sustains a racially unjust society which also influences education. The post-pandemic society should take these reflections into account so that it can contribute to the construction of a more equalitarian society.